HBcrAg Levels Are Associated With Virological Response to Treatment With Interferon in Patients With Hepatitis Delta. Issue 3 (24th September 2021) - Sandmann, Lisa; Yurdaydin, Cihan; Deterding, Katja; Heidrich, Benjamin; Hardtke, Svenja; Lehmann, Patrick; Bremer, Birgit; Manns, Michael P.; Cornberg, Markus; Wedemeyer, Heiner; Maasoumy, Benjamin; ,
Abstract : Standard treatment of hepatitis delta virus (HDV) infection remains pegylated‐interferon alfa (peg‐IFNα) in most centers, which is not only associated with rather low efficacy but several adverse events. Hepatitis B core‐related antigen (HBcrAg) is linked to intrahepatic covalently closed circular DNA levels and has previously been suggested as response predictor in IFN‐based treatment of hepatitis B virus (HBV) mono‐infection. This study aimed to investigate the value of HBcrAg in the management of patients with HBV/HDV co‐infection undergoing peg‐IFNα treatment. The Hep‐Net‐International‐Delta‐Hepatitis‐Intervention Trial‐2 study included 120 patients co‐infected with HBV/HDV. Patients were treated for 96 weeks with peg‐IFNα and either tenofovir or placebo. Ninety‐nine patients with HDV‐RNA results 24 weeks after end of treatment (FU24) were included in this analysis, of whom 32 patients (32.3%) had undetectable HDV RNA at FU24. HBcrAg was measured at baseline, week 12, 24, 48, 96, and FU24. HBcrAg levels showed no significant correlation with HDV RNA but were significantly linked to treatment outcome. HBcrAg levels < 4.5 log IU/mL at baseline, week 24, and week 48 had high negative predictive value (NPV) for achieving undetectable HDV RNA at FU24 (81.8%, 87.1% and 95.0%, respectively). Similarly, HBcrAg levels at week 96 were significantly higher in patients with viral relapse until FU24 (3.0 vs. 3.63 log IU/mL; P  = 0.0089). Baseline, week 24, and week 48 HBcrAg levels were also associated with the likelihood of achieving HBsAg level < 100 IU/mL at FU24 (HBcrAg < 3.0 log IU/mL: NPV 91.7%, 90.4% and 92.3%, respectively). Test statistics improved when combining HBcrAg with additional viral and clinical parameters. Conclusion: HBcrAg is linked to treatment response to peg‐IFNα in patients with HBV/HDV co‐infection and could be a promising marker to determine treatment futility.